2004
DOI: 10.1212/01.wnl.0000147292.64051.9b
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department evaluation of ischemic stroke and TIA

Abstract: Neurologists are seldom involved with acute cerebrovascular care in the emergency department (ED), especially in patients with TIA. Greater neurologist involvement may improve acute stroke diagnosis and treatment efforts in the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 19 publications
5
35
1
2
Order By: Relevance
“…Previous studies support neurologist involvement in the ED as a way to improve acute stroke diagnosis, although this may not be feasible at all institutions. 15,16 In order for a neurologist to be consulted though, the ED has to first consider stroke. An atypical stroke symptom such as nausea/vomiting may not trigger a neurology consult or even an initial neurological examination.…”
Section: March 2016mentioning
confidence: 99%
“…Previous studies support neurologist involvement in the ED as a way to improve acute stroke diagnosis, although this may not be feasible at all institutions. 15,16 In order for a neurologist to be consulted though, the ED has to first consider stroke. An atypical stroke symptom such as nausea/vomiting may not trigger a neurology consult or even an initial neurological examination.…”
Section: March 2016mentioning
confidence: 99%
“…Although some 16,17 but not all studies 18 have shown less access to specialist (neurologist) care for minority stroke patients in the emergency department or hospital setting, few studies have assessed racial/ethnic differences in more general access measures and in a population-based fashion. Among US veterans hospitalized with ischemic stroke, outpatient utilization of both general medicine and neurology in the VA health system was lower for whites compared with blacks, although non-VA Medicare health care utilization was not captured and may have been higher among the older whites.…”
Section: Discussionmentioning
confidence: 99%
“…4 Several studies that have reported on the frequency of IV rt-PA use in both men and women have shown a trend toward women being less likely to receive treatment. These reports have included a wide range of study designs including prospective studies from academic medical centers, 5,6 or community-based hospitals, 7 retrospective studies from community-based hospitals, 8,9 stroke registries, 10 -12 and administrative databases. 13,14 Although previous reviews have suggested that that the use of IV rt-PA is lower in women, 15 as far as we are aware, no systematic review or meta-analysis has been conducted to determine whether there is a genderbased disparity in the use of IV rt-PA for acute ischemic stroke, and whether such a discrepancy is a consistent finding across studies.…”
mentioning
confidence: 99%